Effect of inflammatory factor‐induced cyclo‐oxygenase expression on the development of reperfusion‐related no‐reflow phenomenon in acute myocardial infarction. (February 2015) - Jiao, Qibin; Ke, Qiang; Li, Weiwei; Jin, Meihua; Luo, Yan; Zhang, Linan; Yang, Dong; Zhang, Xingwei
Summary No reflow after reperfusion therapy for myocardial infarction is a strong predictor of clinical outcome. Increased levels of inflammatory factors, including C‐reactive protein (CRP), in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI) may affect myocardial perfusion. However, why the no‐reflow phenomenon increases in inflammation stress after PCI is not clear. The aim of the present study was to determine the effects and molecular mechanisms underlying the effects of CRP on the expression of cyclo‐oxygenase (COX) on the development of the no‐reflow phenomenon. There was a significant increase in plasma levels of CRP and interleukin (IL)‐6 in no‐reflow patients, suggesting that inflammatory factors play an important role in the development of the no‐reflow phenomenon. The mechanisms involved were further evaluated after reperfusion in a rat model mimicking the no‐reflow phenomenon. Compared with normal reflow rats, there were significant increases in both COX‐1 and COX‐2 in cardiac tissue from no‐reflow rats. The COX inhibitor indomethacin (5 mg/kg, i.p.) significantly reduced the no‐reflow area. In another series of experiments, human coronary artery endothelial cells (HCAEC) were treated with CRP at clinically relevant concentrations (5–25 μg/mL). C‐Reactive protein significantly increased COX‐1 and COX‐2 levels in a time‐ and concentration‐dependent manner. In addition, extracellular signal‐regulated kinase (ERK) and Jun N‐terminal kinase (JNK) were activated in CRP (5, 10, 25 μg/mL)‐treated HCAEC cultures. Furthermore, the ERK inhibitor pd98059 (30 μmol/L) and the JNK inhibitor sp600125 (10 μmol/L) blocked CRP‐induced COX‐1 and COX‐2 expression for 12 h. Together, the findings of the present study suggest that CRP can promote the development of the no‐reflow phenomenon by increasing COX‐1 and COX‐2 expression, which is regulated, in part, via ERK and JNK activity.